Coronary arteritis: a case series. Issue 2 (17th February 2020) - Kikuchi, Shinnosuke; Okada, Kozo; Hibi, Kiyoshi; Maejima, Nobuhiko; Yabu, Naoto; Uchida, Keiji; Tamura, Kouichi; Kimura, Kazuo
Abstract: Background: The present article describes two cases of patients with coronary arteritis (CA) whose identification of CA diagnosis (late vs. early) resulted in different clinical courses and outcomes. Case summary: Case 1 is a 53-year-old woman with multiple coronary risk factors who was admitted with acute coronary syndrome (ACS) and significant stenosis in the left main trunk (LMT). Although clues suggested arteritis (LMT lesion without any other stenosis, occlusion of left internal thoracic artery, etc.), the diagnosis of CA (coronary involvement of unclassified arteritis) was delayed and revascularization, including coronary artery bypass grafting (CABG) and percutaneous coronary intervention (PCI), was performed under uncontrolled inflammatory status. As a result, Case 1 experienced repeated ACS episodes due to graft failure and in-stent restenosis, and repeatedly underwent PCI. Case 2 is a 76-year-old woman with no significant coronary risk factors who was admitted with ACS. This patient was successfully diagnosed with coronary involvement of Takayasu arteritis before revascularization. Coronary artery bypass grafting was performed after stabilizing inflammation with prednisolone, and the patient remains angina-free beyond 1-year post-CABG. In both cases, intravascular imaging clearly identified the localization and degree of inflammation related to CA by demonstrating specific findings (ambiguous typical three-layer structure of arterial wall and extended low-echoic areas within adventitia). Discussion: Accurate and early diagnosis with meticulous diagnostic and therapeutic strategies appear to be important for favourable clinical outcomes in the medical treatment of patients with coronary involvement of arteritis. Intravascular imaging has the potential to contribute to optimizing clinical management of CA.